Buffer Overflow Vulnerabilities and Prevention (INTERANTIONAL JOURNAL OF SCIENTIFIC RESEARCH IN ENGINEERING AND MANAGEMENT, 2022)
Either in terms of software error or being an attack itself, buffer overflow attacks have been one of the most important security problems accountable for a common vulnerability of software security and cyber risks. Buffer overflow vulnerabilities influence the zone of remote network penetration vulnerabilities, where an anonymous user tries to gain partial or complete control of the host. Buffer overflow attacks liable for some of the biggest data breaches in recent years. One of the notable data breach examples include Morris worm or internet worm of November 2, 1988. Morris worm is an ancient computer worm distributed via the internet, was noted for infecting around 6000 major Unix machines. This paper mainly focuses on buffer overflow attack vulnerabilities and the preventive measures to safeguard once system from being attacked. Keywords – Buffer overflow attack, susceptibility, impediment